MODIFYING FAT DIET IN PREGNANT AND LACTATANT WOMEN: DOSE IT AFFECT ON NEONATAL AND INFANTILE LIPID PROFILE? - M MOHAMMADIFARD; F MEHRABIAN; N SARAFZADEGAN; F SAJADI; A ABDAR; R KELISHADI; R BASHARDOOST; H SAMARIAN (Journal of Research in Medical Sciences, 2001)
Introduction: Transferred fats from utroplacental barrier have different concentration about their saturation degree. So, the diet during pregnancy seems to have an important role in determining the serum lipid level of the fetus. This study investigated the influence of modifying the maternal dietary fat on the serum lipids of the cord and one year old infants.
Methods: This single blind randomized clinical trail was done on 180 pregnant women who was at 4th month gestational age. All subjects proved to have a fat unmodified diet through a 4-day food record dietary questionnaire. We divided them randomly in two groups. The intervention group was kept on a fat-modified diet including saturated fatty acid < 10 percent, monounsaturated fatty acids: 10-15 percent, polyunsaturated fatty acid up to 10 percent and cholesterol <300 mg/day as well as a dietary advice for the pregnancy period. The control group were given. only the latter advice. All subjects were followed up monthly. The blood samples were done at delivery from cords and after one year from infants. The serum lipids including total cholesterol (T.cho), triglyceride (TG), and HDL cholesterol (HDL-C) were analyzed through enzymatic methods. The level of LDL-cholesterol (LDL-C) was calculated by Friedewald formula.
Results: The mean level of T.cho in the interventional and control group was 70.3±15. 9,81.4±17.2 mg/dl, respectively (P<0.01). TG (85.3±16.7 VS 97.5± 18.2 mg/dl), LDL-C(27.8 ± 15.2 VS 34.8± 17.1 mg/dl) and non-HDL-C (44.5±7.2 VS 54.5 ± 8.1) wre higher in cord blood samples of unmodified dietary fat. In one year old infant the comparison of serum lipids were as follow: T.cho (145.7 ± 51.4 VS 161.4 ± 56.2, P<0.003), TG (90.1 ± 31.8 VS 98.3±33.1, P<0.02), LDL-C (85.6± 20.4 VS 92.3±19.6, P < 0,05) and non-HDL-C (113.6±30.2 VS 128.8±34.8,P < 0.04). There was no significant difference in HDL-C.
Discussion: According to the results, there is a significant decrease of T.cho, TG, LDL-C and non-HDL-C levels with no significant increase of HDL-C in the intervention group with the fat-modified diet. We conclude that the modifying maternal fat diet could be suitable way to prevent cardiovascular disease.